2022
DOI: 10.6004/jnccn.2022.7032
|View full text |Cite
|
Sign up to set email alerts
|

Extended HPV Genotyping for Risk Assessment of Cervical Intraepithelial Neoplasia Grade 2/3 or Worse in a Cohort Study

Abstract: Background: We sought to identify the absolute risk of specific HPV genotype for cervical intraepithelial neoplasia grade 2/3 or worse (CIN2+/3+) and to develop a risk-based management strategy in an HPV-positive population. Methods: HPV genotyping was performed based on a 3-year cervical cancer screening cohort. The study endpoints were histologic CIN2+/3+. The prevalence of specific HPV genotype was calculated by minimum, any type, and hierarchical attribution estimate. The absolute CIN2+/3+ risks of specifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 43 publications
0
4
0
2
Order By: Relevance
“… 32 , 33 Previous studies have investigated the HPV genotype distribution among Chinese women but most were based on a single center or healthcare institutions, limiting their ability to provide representation of general population. 9 , 29 , 34 , 35 , 36 , 37 , 38 In this study, we used pooled data from nine population‐based cervical cancer screening studies from six parts of China and identified that the five most frequently detected genotypes were HPV52, 16, 58, 68, and 51. We further evaluated HPV genotype distribution stratified by pathology grade as a proxy for risk assessment to identify genotypes that warrant distinct management.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“… 32 , 33 Previous studies have investigated the HPV genotype distribution among Chinese women but most were based on a single center or healthcare institutions, limiting their ability to provide representation of general population. 9 , 29 , 34 , 35 , 36 , 37 , 38 In this study, we used pooled data from nine population‐based cervical cancer screening studies from six parts of China and identified that the five most frequently detected genotypes were HPV52, 16, 58, 68, and 51. We further evaluated HPV genotype distribution stratified by pathology grade as a proxy for risk assessment to identify genotypes that warrant distinct management.…”
Section: Discussionmentioning
confidence: 99%
“…It has been established that HPV genotype distribution varied greatly by geographic region, with HPV‐16 retaining the most common type globally but HPV52 and 58 being more prevalent in Eastern Asia 32,33 . Previous studies have investigated the HPV genotype distribution among Chinese women but most were based on a single center or healthcare institutions, limiting their ability to provide representation of general population 9,29,34–38 . In this study, we used pooled data from nine population‐based cervical cancer screening studies from six parts of China and identified that the five most frequently detected genotypes were HPV52, 16, 58, 68, and 51.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Una revisión sistemática de 236 fuentes identificadas con 76 artículos completos recuperados publicada en el año 2020 32 muestra evidencia que respalda la utilidad clínica de caracterizar otros genotipos de VPH-AR, además de los 16 y 18, lo cual podría ser costo-efectivo 32 . En un estudio de cohortes, de Li, X y cols., en 2022 35 , se concluyó que la estrategia de manejo basada en el riesgo…”
Section: Discussionunclassified